Genome size variation of southern South American species of Ilex (Aquifoliaceae) - Garberoglio, Mariana Julia (2023)
The genus Ilex (Aquifoliaceae) has several species appreciated by their ornamental value and nutraceutical and medicinal properties. Southern South America is a major center of biodiversity, with ca. 13-15 species. However, they have been scarcely studied, particularly regarding cytogenetics. For instance, chromosome numbers have been solely documented in eight species, while the DNA content (genome size or 2C-value) has been recorded just for three species. To contribute to the characterization of Ilex species from southern South America, here we established the genome size of I. brasiliensis, I. brevicuspis, I. integerrima, I. microdonta, I. pseudobuxus, I. taubertiana and I. theezans as novel data, and verified the DNA content for I. argentina, I. dumosa and I. paraguariensis. Our results indicate that the mean DNA content at the interspecific level ranges between 1.691 pg, as in I. pseudobuxus and 3.600 pg as in I. theezans. Yet, an individual of I. theezans from Paraguay showed about half the genome size. These unexpected outcomes for I. theezans lead us to propose the coexistence of diploid and polyploid cytotypes for this species. I. brasiliensis was determined to have 2n=40 chromosomes and regular meiosis, for the first time. In sum, this work is a contribution to the knowledge of an understudied plant family. Gaining insight on genetic biodiversity is relevant for the potential use of non-industrialized species for the improvement of economically significant ones.